Developmental Trajectories of Justice System-Involved Friendship Proportion: Relevance for Predicting Continued Offending Risk in Emerging Adulthood - Wojciechowski, Thomas (Criminal justice review, 2022)
There is limited research which has examined the developmental nature of friendships and their relevance for offending. This study examined heterogeneity in the development of justice system-involved friendship proportionality and its relevance for predicting offending continuity in emerging adulthood. Having a greater proportion of such peers within a friendship collective as individuals exit adolescence may lead to continued risk of offending in adulthood. The Pathways to Desistance data were used in analyses. Group-based trajectory modeling was used to identify developmental patterns of justice system-involved friendship proportionality during adolescence and emerging adulthood. Logistic regression was used to assess the relevance of trajectory group assignment for predicting offending risk in emerging adulthood. Findings indicated that a six-group trajectory model best fit the data. All other trajectory groups in the model indicated a lower risk of offending in emerging adulthood than the High Chronic justice system-involved friendship proportionality group. Sensitivity analyses indicated that separation from criminal peers following adolescence may be a more conservative predictor of offending risk in emerging adulthood.